FACTORS AFFECTING THE DECISION TO TAKE CREDIT CUSTOMERS FUTURE PROGRAM PACKAGE ( PMD) IN BANK BTPN SYARIAH (CASE STUDY AT THE STATE SAVING BANK SYARIAH PAMULARSIH KCS) - Muhamad Ali Mukhson; Maria Magdalena Minarsih; Moh Mukeri Warso (Jurnal Ekonomi dan Bisnis Kontemporer, 2016)
his research aimed to analyze the influence of the variable service, adminfees, location, interest rates, the procedures of the customer's decision. Thepopulation in this study are all the people who never took credit in the bank. Thesample in this study were 105 people who never took the credit in the bank. Theanalytical tool used in this research is multiple regression analysis, t-test, F andcoefficient of determination (R ²).Based on the test results of the coefficient of determination (R²) of 0556which showed that the correlation or relationship between the variables a client'sdecision (the dependent variable) with a variable service, admin fees, locations,rates, procedure (independent variable) has the degree of correlation of 55.6%the balance of 44.4 % influenced by other variables outside variables studied. Theresults of hypothesis testing can be known magnitude F count variable service,admin fees, locations, rates, procedure together have an influence on thecustomer's decision to take the credit. The results of t test analysis showed that thevariables of service, the interest rate, does not significantly affect the customer'sdecision to take the credit. Meanwhile, admin fees, locations, proceduressignificant positive effect on the customer's decision to take the credit. Theseresults also indicate that.Keywords: service, the interest rate, admin fees, locations, procedures, take thecredit